Implementasi Pengamanan Data Menggunakan Kombinasi Algoritma Kriptografi AES-256 dan Teknik Steganografi End-of-File (EOF) Pada Media Citra Digital - Jakbar Ali Harahap; Muhammad Aulia; Muhammad Rasyya Alfarisi; Soty Sohaimi (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
In the contemporary digital landscape, the security and confidentiality of information exchange have emerged as paramount concerns due to the increasing sophistication of cyber threats. This study proposes an integrated security framework through the development of